A Rare Variant of ANK3 Is Associated With Intracranial Aneurysm - Liu, Junyu; Liao, Xin; Zhou, Jilin; Li, Bingyang; Xu, Lu; Liu, Songlin; Li, Yifeng; Yuan, Dun; Hu, Chongyu; Jiang, Weixi; Yan, Junxia (Frontiers in Neurology, 2021)
Intracranial aneurysm (IA) is a cerebrovascular disorder in which abnormal dilation of a blood vessel results from weakening of the blood vessel wall. The aneurysm may rupture, leading to subarachnoid hemorrhage with severe outcomes. This study was conducted to identify the genetic factors involved in the etiology of IA. Whole-exome sequencing was performed in three IA-aggregate families to identify candidate variants. Further association studies of candidate variants were performed among sporadic cases and controls. Bioinformatic analysis was used to predict the functions of candidate genes and variants. Twenty variants were identified after whole-exome sequencing, among which eight were selected for replicative association studies. ANK3 c.4403G>A (p.R1468H) was significantly associated with IA (odds ratio 4.77; 95% confidence interval 1.94–11.67; p-value = 0.00019). Amino acid R1468 in ANK3 was predicted to be located in the spectrin-binding domain of ankyrin-G and may regulate the migration of vascular endothelial cells and affect cell–cell junctions. Therefore, the variation p.R1468H may cause weakening of the artery walls, thereby accelerating the formation of IA. Thus, ANK3 is a candidate gene highly related to IA.